Analisis Penyelenggaraan Seminar Pariwisata sebagai Kegiatan MICE: Studi pada Seminar yang dilaksanakan Mahasiswa Magister Pariwisata STIPRAM - Randa Surya Dinata; Rany Surya Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
Academic seminars in the field of tourism are generally regarded as educational activities; however, in practice, they exhibit characteristics aligned with the Meetings, Incentives, Conferences, and Exhibitions (MICE) industry, particularly within the Meeting/Conference category. This study aims to analyze the suitability of Tourism Seminars as MICE activities and to evaluate participants’ perceptions of the quality of their organization. The research employed a descriptive quantitative approach using a survey method. Data were collected through closed-ended Likert-scale questionnaires distributed to 95 seminar participants who attended the event both offline and online (hybrid). Pearson Product Moment validity testing and Cronbach’s Alpha reliability testing were conducted prior to the use of the research instrument. The results indicate that all questionnaire items were valid, with r-calculated values exceeding the r-table value (0.202), and reliable, with a Cronbach’s Alpha coefficient of 0.886. Descriptive analysis shows that all assessment indicators—including event planning and organization, participant management, facilities and technology, event implementation, fulfillment of MICE elements, and benefits and competency development—achieved mean scores in the “very good” category. These findings demonstrate that the seminar was professionally organized and met the standards of MICE activities within the Meeting/Conference subcategory. This study concludes that academic seminars have strong potential to be classified as MICE activities when managed formally and systematically, and can serve as an effective experiential learning medium for developing human resource competencies in the tourism MICE sector.